1999
DOI: 10.1089/thy.1999.9.1175
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Absent Thyroid Peroxidase Antibodies and High Thyroid-Stimulating Immunoglobulin Levels in Graves' Disease Identifies a Group at Markedly Increased Risk of Ophthalmopathy

Abstract: Among Graves' Disease (GD) patients, we have observed an unexpectedly high prevalence of antithyroperoxidase antibody (TPOAb) and antithyroglobulin antibody (TgAb) negativity in those with severe ophthalmopathy. To study the possible role of thyroid autoantibodies in the pathogenesis of Graves' ophthalmopathy (GO), TPOAb, TgAb, thyroid-stimulating immunoglobulin (TSI), and thyrotropin-binding inhibitory immunoglobulin (TBII) levels were measured, and the presence or absence of GO was assessed by a single obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 44 publications
6
83
3
Order By: Relevance
“…Many study showed that thyroid binding inhibitor immunoglobulin or thyroid-stimulating antibody are involved in the etiology of TAO. [15][16][17] In present study, TBII levels were positive in most of TAO patients (96.25% and 90.0% in mild-moderate TAO and severe TAO respectively).…”
Section: Discussionsupporting
confidence: 57%
“…Many study showed that thyroid binding inhibitor immunoglobulin or thyroid-stimulating antibody are involved in the etiology of TAO. [15][16][17] In present study, TBII levels were positive in most of TAO patients (96.25% and 90.0% in mild-moderate TAO and severe TAO respectively).…”
Section: Discussionsupporting
confidence: 57%
“…We hypothesized that these antibodies might modulate TRAb effects on GO (7). How TPOAb might affect the orbit is unknown and the presence of TPO at that site has not been previously described.…”
Section: Introductionmentioning
confidence: 98%
“…According to previous reports, titers of TSAb, but not of TBII, are significantly higher in patients with Graves' ophthalmopathy than in patients without Graves' ophthalmopathy [19], and the severity of Graves' ophthalmopathy is correlated with TSAb titers [9]. Although the absence of TPOAb is associated with a 5-fold increased risk of Graves' ophthalmopathy, the presence of TPOAb or TgAb is not a risk factor for Graves' ophthalmopathy [20]. These findings suggest that of the autoimmune antibodies detected in this case, TSAb is the most likely to be related to the development of Graves' ophthalmopathy.…”
Section: Discussionmentioning
confidence: 88%